Salinity-Linked Denitrification Potential in Endorheic Lake Bosten (China) and Its Sensitivity to Climate Change - Jiang, Xingyu; Liu, Changqing; Hu, Yang; Shao, Keqiang; Tang, Xiangming; Gao, Guang; Qin, Boqiang (Frontiers in Microbiology, 2022)
Endorheic lakes in arid regions of Northwest China are generally vulnerable and sensitive to accelerated climate change and extensive human activities. Therefore, a better understanding of the self-purification capacity of ecosystems, such as denitrification, is necessary to effectively protect these water resources. In the present study, we measured unamended and amended denitrification rates of Lake Bosten through adding the ambient and extra nitrate isotopes (100 μmol L−1) in slurry incubations. Meanwhile, we investigated the abundances and community structure of nitrous oxide-reducing microorganisms using qPCR and high-throughput sequencing, respectively, in the surface sediments of Lake Bosten to study denitrification potential in endorheic lakes of arid regions as well as the response of those denitrifiers to climatically induced changes in lake environments. Amended denitrification rates increased by one order of magnitude compared to unamended rates in Lake Bosten. The great discrepancy between unamended and amended rates were attributed to low nitrate availability, indicating that Lake Bosten is not operating at maximum capacity of denitrification. Salinity shaped the spatial heterogeneity of denitrification potential through changes in the abundances and species diversity of denitrifiers. Climate change had a positive effect on the water quality of Lake Bosten so far, through increased runoff, decreased salinity and enhanced denitrification. But the long-term trajectories of water quality are difficult to predict alongside future glacier shrinkage and decreased snow cover.